Gan Photonic Crystals: Spectral Dynamics in UV, X‐Ray, and Alpha Radiation - Firat Yasar; Noriaki Kawaguchi; Takayuki Yanagida; Isabel Harrysson Rodrigues; Yleana Evelyn Ceballos; Roberto Prado‐Rivera; Sam Keo (Advanced Photonics Research)
In this work, a comparative analysis of gallium nitride (GaN) thin films is conducted, both with and without photonic crystal (PhC) structures, focusing on their scintillation and photoluminescence properties. GaN's suitability for diverse optoelectronic and radiation detection applications is analyzed, and this study examines how PhC implementation can enhance these properties. Methodologically, the emission spectra is analyzed from 5.9 keV X‐ray sources, decay curves, pulse height spectra in response to 241Am 5.5 MeV alpha‐rays, and photoluminescence spectra induced by UV excitation. The findings demonstrate a substantial increase in quantum efficiency for PhC GaN, nearly tripling the light yield that of conventional plain GaN thin films under the UV excitation. The enhancement is predominantly attributed to the PhC GaN's proficiency in guiding light at 550 nm, a feature indicative of its spectral filtering capabilities, as detailed in the study. Furthermore, side‐band scintillations, stemming from inherent materials like Chromium that generate scintillations at diverse wavelengths, are effectively mitigated. A key finding of this study is the effective detection of light not only at the rear but also along the lateral sides of the films, offering new possibilities for radiation detector design and architecture.